The Role of Big Data Analytics in Financial Decision - Making - Owais Ahmad,; Prof. Jaideep Sharma, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In today's rapidly evolving financial landscape, the integration of big data analytics has become a transformative force in shaping strategic decision-making processes. This study explores the significant role that big data analytics plays in financial decision making, with a focus on how financial institutions, corporations, and investors leverage data-driven insights to enhance accuracy, efficiency, and risk management. The research examines the various components of big data, including volume, velocity, variety, and veracity, and how these dimensions contribute to more informed financial analysis. It also highlights the application of advanced analytical tools such as predictive analytics, machine learning algorithms, and real – time data processing in areas such as credit risk assessment, fraud detection, investment strategies, and financial forecasting. Through a combination of literature review, case studies, and industry analysis, this project underscores the growing importance of big data analytics as a strategic asset in financial management. The findings suggest that organizations that effectively harness big data are better positioned to make timely, accurate, and forward-looking financial decisions. The findings suggest that when effectively implemented, big data analytics empowers financial professionals to make more accurate, timely, and forward-looking decisions, ultimately contributing to better financial performance and customer satisfaction.
Keywords: Big Data Analytics; Financial Decision Making; Predictive Analytics; Risk Management; Real-time Data Processing